PENGARUH PEMBERIAN KOMPRES HANGAT PADA PUNGUNG BAWAH IBU INPARTU KALA 1 FASE AKTIF TERHADAP TINGKAT NYERI DI RUANG BERSALIN RUMAH SAKIT ISLAM JOMBANG: The Effect Of Giving Warm Compress On The Level Of Pain In The Delivery Ward In Islamic Hospital Jombang - Mochamad Farip, Siti Junaidah (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2024)
There are two methods of dealing with labor pain, namely medical and non-medical. One of the non-medical actions is the provision of warm compresses given to the lower back area. Giving warm compresses can improve blood circulation, provide a feeling of warmth, prevent muscle spasms and reduce pain. This research is based on the results of observations made at the Jombang Islamic Hospital that the methods used to treat pain in laboring mothers are back massage and providing emotional support, while warm compresses have never been applied. This study aims to determine the effect of warm compresses on the level of active phase I labor pain in the Delivery Room of Jombang Islamic Hospital in 2023.                    The design of this study used the Quasi Experiment method (pseudo-experiment), with a one group pretest posttest design. The sample of this study was 15 women giving birth normally at the Jombang Islamic Hospital in July 2023. The results of the study were that most (66.7%) of respondents had severe pain before being given warm compresses and almost all (80%) of respondents had moderate pain levels after being given warm compresses. The results of the Wilcoxon statistical test obtained a p value of 0.001 (?<0.05) so it can be concluded that there is an effect of warm compresses on the level of labor pain in the Delivery Room of the Jombang Islamic Hospital. Provision of warm compresses can be applied in the Delivery Room of Jombang Islamic Hospital to help reduce labor pain, provide a sense of comfort and relaxation for mothers in labor.